Dynamic modeling of absorption/desorption closed-loop including periphery - Bothe, Mike; Hami Dindar, Iman; Lutters, Nicole; Kenig, Eugeny Y. (Computers and Chemical Engineering)

A PLIC-based method for species mass transfer at free fluid interfaces - Schulz, Andreas Markus; Wecker, Christian; Inguva, Venkatesh; Lopatin, Alexey S.; Kenig, Eugeny Y. (Chemical Engineering Science)

Droplet formation –a numerical investigation of liquid-liquid systems with consideration of Marangoni convection - Wecker, Christian; Schulz, Andreas Markus; Heine, Jens; Bart, Hans Jörg; Kenig, Eugeny Y. (International Journal of Heat and Mass Transfer)

Experimentelle Untersuchung der Tropfenkondensation am chemisch modifizierten Edelstahl‐Drallrohr - Dai, Daokun; Kenig, Eugeny Y.; Numrich, Reiner (Chemie Ingenieur Technik)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

A front-tracking method for two-phase flow simulation with no spurious currents - Inguva, Venkatesh; Kenig, Eugeny Y.; Perot, J. Blair (Journal of Computational Physics)

Determination of the burst pressure of pillow plates using finite element methods - Zibart, Alexander; Spang, Bernhard; Kenig, Eugeny Y. (Computer Aided Chemical Engineering)

Flow in Pillow-Plate Channels for High-Speed Turbomachinery Heat Exchangers - Sundermeier, Stephan; Passmann, Maximilian; aus der Wiesche, Stefan; Kenig, Eugeny Y. (International Journal of Turbomachinery, Propulsion and Power)
In numerous turbomachinery applications, e.g., in aero-engines with regenerators for improving specific fuel consumption (SFC), heat exchangers with low-pressure loss are required. Pil low-plate heat exchangers (PPHE) are a novel exchanger type and promising candidates for high-speed flow applications due to their smooth profiles avoiding blunt obstacles in the flow path. This work deals with the overall system behavior and gas dynamics of pillow-plate channels. A pillow-plate channel was placed in the test section of a blow-down wind tunnel working with dry air, and compressible flow phenomena were investigated utilizing conventional and focusing schlieren optics; furthermore, static and total pressure measurements were performed. The experiments supported the assumption that the system behavior can be described through a Fanno–Rayleigh flow model. Since only wavy walls with smooth profiles were involved, linearized gas dynamics was able to cover important flow features within the channel. The effects of the wavy wall structures on pressure drop and Mach number distribution within the flow path were investigated, and a good qualitative agreement with theoretical and numerical predictions was found. The present analysis demonstrates that pressure losses in pillow-plate heat exchangers are rather low, although their strong turbulent mixing enables high convective heat transfer coefficients.
Keywords: Mechanical Engineering; Energy Engineering and Power Technology; Aerospace Engineering

State-of-the-Art Modeling of Separation Columns: A Review - Kenig, Eugeny Y. (Chemical Engineering Transactions)

Wässrige Aminozuckerlösungen als neue Lösungsmittel zur CO2-Abscheidung - Hami Dindar, Iman; Baumhögger, Elmar; Lutters, Nicole; Kenig, Eugeny (Jahrestreffen der ProcessNet Fachgruppen Fluidverfahrenstechnik und Hochdruckverfahrenstechnik)

Flow Morphology of TEG Desiccant in a Structured Packing Air Dehumidifier Exposed to Floating Conditions - Mamedov, Tural; Schleicher, Eckhard; Schubert, Markus; Ehlert, Thomas; Kenig, Eugeny Y.; Hampel, Uwe (Proceedings of the 12th international conference Distillation & Absorption 2022)

On methods to reduce spurious currents within VOF solver frameworks. Part 1: a review of the static bubble/droplet - Inguva, Venkatesh; Schulz, Andreas; Kenig, Eugeny (Chemical Product and Process Modeling)
Abstract In two-phase flows in which the Capillary number is low, errors in the computation of the surface tension force at the interface cause Front-Capturing methods such as Volume of Fluid (VOF) and Level-Set (LS) to develop interfacial spurious currents. To better solve low Capillary number flows, special treatment is required to reduce such spurious currents. Smoothing the phase indicator field to more accurately compute the curvature or adding interfacial artificial viscosity are techniques that can treat this problem. This study explores OpenFOAM, Fluent and StarCCM+ VOF solvers for the classical case of a static bubble/droplet immersed in a continuous aqueous phase, with the focus on the ability of these solvers to adequately reduce spurious currents. The results are expected to be helpful for practicing chemical engineers who use multiphase CFD solvers in their work.

Modelling and simulation of zero-gravity distillation units with metal foams - Wende, Marc; Staggenborg, Christoph; Kenig, Eugeny Y. (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Model Based and Experimental Analysis of the Dynamic Reactive Absorption Loop Behavior - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny Y. (Proceedings of the 12th international conference Distillation & Absorption 2022)

Modeling Concepts for Reactive Separations - Kenig, Eugeny Y. (Process Intensification by Reactive and Membrane-assisted Separations)

Modelling film and rivulet flows on microstructured surfaces using CFD methods - Bertling, René; Hack, M.; Ausner, I.; Horschitz, B.; Bernemann, Sören Antonius; Kenig, Eugeny (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Numerical and Experimental Investigation of Zero-Gravity Distillation Units - Wende, Marc; Fischer, Florian; Kenig, Eugeny (Chemical Engineering Transactions)

Examination of hazardous situations in industrial closed-loop processes using dynamic simulations - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny (Chemical Engineering Transactions)

Numerical and Experimental Investigation of Zero-Gravity Distillation Units - Wende, Marc; Fischer, Florian; Kenig, Eugeny (24th Conference on Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction (PRES‘21))

Konzeption und Inbetriebnahme eines Versuchsstandes zur Gravidestillation - Wende, Marc; Kenig, Eugeny (Jahrestreffen der ProcessNet-Fachgruppen Fluidverfahrenstechnik und Wärme- und Stoffübertragung)

Modellierung eines Latentwärmespeichersystems in Form einer ungeordneten Schüttung makro-verkapselter PCM-Elemente - Grabo, Matti; Kenig, Eugeny